Mixed embeddedness and entrepreneurship beyond new venture creation: Opportunity tensions in the case of reregulated public markets. (March 2023) - Högberg, Lena; Mitchell, Craig
The mixed embeddedness (ME) perspective offers a holistic approach to understanding entrepreneurship as embedded in a myriad of contexts. Alone, however, it is not capable of explaining the dynamic interrelations between entrepreneurship and opportunity structures beyond venture start-up. We offer a synthesis between ME and the dynamic states approach, using the concept of opportunity tension to explore the recursive interplay between entrepreneurial agency and opportunity structures. The integrated approach is applied to, and developed by drawing upon, the case of ethnic minority entrepreneurship in the changing Swedish welfare state following customer choice reform. We explore opportunity tensions that arise during start-up, growth and exit for two firms that provide care for the elderly in public quasi-markets. We develop concepts that account for different patterns of embeddedness and opportunity tensions as well as bottom-up effects of entrepreneurship in terms of reregulation and conclude that the interplay amounts to a paradox of ethnicity.